La réception des films de la Nouvelle Vague dans le courrier des lecteurs de Cinémonde - Geneviève Sellier (Communication)
In an attempt to find traces of female spectatorship in the letters to the editor published in the popular French weekly Cinémonde (1928–1966), the author chose the period (1959–1960) that coincided with the emergence of the Nouvelle Vague in cinema. She found among the regular (young) readers of this popular magazine a swell of comments and exchanges. Selected quotes from these letters reveal that these moviegoers do articulate ethical and aesthetic points of view when commenting on the actors’ performance, the movie’s “lesson in life” and the innovative aspects of the direction.